2017
DOI: 10.1155/2017/8204353
|View full text |Cite
|
Sign up to set email alerts
|

Using UAV-Based Systems to Monitor Air Pollution in Areas with Poor Accessibility

Abstract: Air pollution monitoring has recently become an issue of utmost importance in our society. Despite the fact that crowdsensing approaches could be an adequate solution for urban areas, they cannot be implemented in rural environments. Instead, deploying a fleet of UAVs could be considered an acceptable alternative. Embracing this approach, this paper proposes the use of UAVs equipped with off-the-shelf sensors to perform air pollution monitoring tasks. These UAVs are guided by our proposed Pollution-driven UAV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 38 publications
0
60
0
3
Order By: Relevance
“…There are further examples of sensors used for trace gas deployment that do not explicitly stick to one type of detection mechanism, several examples of UAS deployments for atmospheric monitoring can be found in the literature [46][47][48][49][50][51][52][53][54]. For calibration purposes, the measured resistivity of the MQ-4 sensor (R s ) is expressed relative to the reference signal for 1000 ppmv CH 4 in air (R o ) [43].…”
Section: Implementation Of Sensor Technology Onboard Uassmentioning
confidence: 99%
“…There are further examples of sensors used for trace gas deployment that do not explicitly stick to one type of detection mechanism, several examples of UAS deployments for atmospheric monitoring can be found in the literature [46][47][48][49][50][51][52][53][54]. For calibration purposes, the measured resistivity of the MQ-4 sensor (R s ) is expressed relative to the reference signal for 1000 ppmv CH 4 in air (R o ) [43].…”
Section: Implementation Of Sensor Technology Onboard Uassmentioning
confidence: 99%
“…Previous published work has demonstrated that drones can be used to acquire air pollution concentrations (Altstadter et al, 2015;Alvear et al, 2017;Babaan et al, 2018;Berman et al, 2012;Brady et al, 2016;Chang et al, 2018;Chilinski et al, 2018;Corrigan et al, 2008;Fladeland et al, 2011;Gu et al, 2018;Illingworth et al, 2014;Lawrence and Balsley, 2013;Mayer et al, 2012;Ramana et al, 2007;Ramanathan, 2006;Ruiz-Jimenez et al, 2019;Reuder et al, 2012;Smidi and Hofman, 2013;www.scmp.com;Villa et al, 2016;Vo et al, 2018;Watai et al, 2006). However, the ability of a drone to automatically detect when the concentration of a pollutant has exceeded the recommended threshold has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Drones have been investigated as a means to detect environmental air pollution (Altstadter et al, 2015;Brady et al, 2016;Chang et al, 2018;Chilinski et al, 2018;Corrigan et al, 2008;Lawrence and Balsley, 2013;Mayer et al, 2012;Ramana et al, 2007;Ramanathan 2006;Reuder et al, 2012;Smidi and Hofman, 2013;www.scmp.com;techrepublic.com;www.auav.com.au;www.nationaldrones.com.au;Villa et al, 2016;Vo et al, 2018;Watai et al, 2006). CO 2 , CH 4 , Particulate Matter (PM), NO 2 , volatile organic compounds (VOCs), ozone, and water vapor concentrations have been successfully measured (Alvear et al, 2017;Babaan et al, 2018;Berman et al, 2012;Fladeland et al, 2011;Gu et al, 2018;Illingworth et al, 2014;Ruiz-Jimenez et al, 2019). UAV vision guided aerial-ground air quality sensing system, to monitor and forecast AQI distributions in spatial-temporal perspectives has been developed by Yang et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…With portable devices appropriately installed on the UAV, it is maneuverable and can collect air quality data in areas where conventional methods are difficult to reach [23]. Based on the UAV platform, the pollution maps can be constructed and the high concentration hotspots can be discovered [24]. It can find the most polluted areas with a higher coverage within the time bounds defined by the UAV flight time [25,26].…”
Section: Introductionmentioning
confidence: 99%